Energy Storage Control Strategy of Railway Network Side Considering Characteristic Harmonic Control - Yanqiang HE; Ying WANG; Xiaoqiang CHEN; Jianxiao CHEN (Zhongguo dianli)
Aiming at the problems of energy saving, efficiency improvement and harmonic control of electric railways, a control strategy of railway traction network-side energy storage system is proposed with consideration of characteristic harmonic control. Firstly, the access scheme of the traction network-side energy storage system is analyzed and its working modes are classified. Secondly, according to the distribution of characteristic harmonics of traction load, a novel method is deduced for peak load shaving and characteristic harmonics control by using the energy storage system at the grid side. And then, a control strategy of supercapacitor energy storage system is proposed, which takes into account the grid-side characteristic harmonic suppression. Finally, the feasibility of the proposed strategy is verified by simulation tests under multiple working conditions. The results show that the proposed strategy can effectively recover the regenerative braking energy, reduce the power fluctuation, and suppress the characteristic harmonics at the grid side.